2020
DOI: 10.15448/1980-6108.2020.1.38509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 patients and the main nursing diagnoses

Abstract: AIMS: to present a reflection on the clinic of patients infected by COVID-19 and to propose the main nursing diagnoses based on International Classification for Nursing Practice (ICNP©). METHOD: this is a reflection study, in which the selection criteria used were articles indexed in the MEDLINE, LILACS and BDENF databases published between December 2019 and April 2020, in English and Portuguese. RESULTS: 10 scientific articles were part of the study, which made it possible to know the symptomatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…2021) and mapped to the standardised nursing languages NANDA‐I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID‐19 patients ( de Souza et al., 2020; Santos et al., 2021).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…2021) and mapped to the standardised nursing languages NANDA‐I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID‐19 patients ( de Souza et al., 2020; Santos et al., 2021).…”
Section: Introductionmentioning
confidence: 87%
“…Two studies using clinical data showed the value of using standardised terminologies, such as Omaha and NANDA-I, when describing nursing care of COVID-19 patients (Ardic & Turan, 2021;Asghari et al, 2021). Moreover, terms relevant to the context of COVID-19-hospitalised patients have been identified from the literature (Barros et al 2020;de Souza et al 2020;Menezes et al 2021;Santos et al, 2021), official documents (Aguña et al 2021a(Aguña et al , 2021bAraújo et al 2021) and care plans (Swanson et al 2021) and mapped to the standardised nursing languages NANDA-I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID-19 patients ( de Souza et al, 2020;Santos et al, 2021).…”
Section: Icnp As a Reference Set In Systematized Nomenclature Of Medi...mentioning
confidence: 99%
See 1 more Smart Citation